2011
DOI: 10.1159/000329340
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Internet Use in Older Primary Care Patients

Abstract: Background: Adults aged 65 years and older stand to benefit from the accumulating wealth of Internet-based health resources, including online interventions to assist in the self-management of chronic health conditions. However, concerns have been expressed that lesser Internet use and familiarity among older adults may limit the utility of web-based health interventions in older age groups. As these interventions become more prevalent, it is important to understand older adults’ receptivity to using the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…27 For comparison, a recent survey of older veterans revealed that over half expressed interest in using the Internet to track goals as well as manage anxiety and depression symptoms. 25 Similar surveys among individuals complaining of anxiety in the United Kingdom found similar results: 90% reported interest in computerized anxiety treatment in one study, and in another, one-half of individuals over the age of 65 years with depression and/or anxiety disorders indicated interest in CPT. 28,29 In addition, the latter studies also support the current finding that individuals interested in CPT were on average 5 years older than those who were not interested in CPT.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…27 For comparison, a recent survey of older veterans revealed that over half expressed interest in using the Internet to track goals as well as manage anxiety and depression symptoms. 25 Similar surveys among individuals complaining of anxiety in the United Kingdom found similar results: 90% reported interest in computerized anxiety treatment in one study, and in another, one-half of individuals over the age of 65 years with depression and/or anxiety disorders indicated interest in CPT. 28,29 In addition, the latter studies also support the current finding that individuals interested in CPT were on average 5 years older than those who were not interested in CPT.…”
Section: Discussionmentioning
confidence: 64%
“…As VHA continues to develop CPT programs in preparation for their implementation and to expand its use of HIT in general, 25 there is a need to evaluate interest in such services and barriers among potential users. The current study surveyed interest in CPT and its relation to the use of information technology in a sample of VHA patients in treatment for substance use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…(51) However, the oldest cohorts of adults who simultaneously have the greatest health needs also have the lowest familiarity with HIT. (19) This group is likely to say that they don't use the Internet or email because it doesn't seem relevant to them—they're “just not interested”—raising the question whether availability of targeted resources could overcome these barriers or not.…”
Section: Familiaritymentioning
confidence: 99%
“…But there are signs that even the older elderly are increasingly using the Internet and are open to doing so for health information. (51)…”
Section: Familiaritymentioning
confidence: 99%
See 1 more Smart Citation